2013
DOI: 10.2460/javma.242.7.936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fiber concentration in dry and canned commercial diets formulated for adult maintenance or all life stages of dogs by use of crude fiber and total dietary fiber methods

Abstract: Among the evaluated diets, measured CF concentration underrepresented measured TDF concentration. Diets provided a wide range of TDF concentration, and proportions of IDF and SDF were variable. In the absence of information regarding TDF concentration, neither reported maximum nor measured CF concentration appears to be a particularly reliable indicator of fiber concentration and composition of a given canine diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
4
9
1
Order By: Relevance
“…Differences between manufacturer-reported maximum moisture concentrations and measured moisture concentrations in the present study were consistent with results of other studies, 26,40,41 as were differences between the reported maximum CF and measured TDF concentration. 26,28,40 In canned diets only, reported maximum CF concentration was not different than measured IDF concentration, suggesting this value could potentially be used to estimate IDF content in similar diets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Differences between manufacturer-reported maximum moisture concentrations and measured moisture concentrations in the present study were consistent with results of other studies, 26,40,41 as were differences between the reported maximum CF and measured TDF concentration. 26,28,40 In canned diets only, reported maximum CF concentration was not different than measured IDF concentration, suggesting this value could potentially be used to estimate IDF content in similar diets.…”
Section: Discussionsupporting
confidence: 92%
“…26,28,40 In canned diets only, reported maximum CF concentration was not different than measured IDF concentration, suggesting this value could potentially be used to estimate IDF content in similar diets. However, this was not supported by a previous study 26 for a sample of canine maintenance diets. Reported CF concentrations in excess of measured TDF and IDF concentrations in canned diets were previously determined in a study 40 evaluating fiber content and composition in feline diets for management of obesity and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 86%
“…In the current study, although using a smaller number of diets, higher in fibre than average dog feed, each percentual unit increase of CF resulted in a TDF increment of two percentual units. In another study with dog food, Farcas et al (2013) found that CF under-represented TDF and was not a good indicator of fibre in the diet, similar to the data presented here. The relatively high correlation observed in our study may be explained by inclusion of similar fibre sources in the test diets.…”
Section: Discussionsupporting
confidence: 88%
“…In another study with dog food, Farcas et al. () found that CF under‐represented TDF and was not a good indicator of fibre in the diet, similar to the data presented here. The relatively high correlation observed in our study may be explained by inclusion of similar fibre sources in the test diets.…”
Section: Discussionsupporting
confidence: 86%
“…Another recent study (FARCAS et al, 2013) evaluates the differences between maximum crude fiber concentrations and total dietary fiber concentrations (which would be the gold standard method currently) in 20 dry and 20 moist non-therapeutic foods for dogs, and the authors concluded that in lack of information on total dietary fiber concentration (as is the case of our study) no crude fiber concentration appears to be a particularly reliable indicator of fiber concentration and composition of a canine diet.…”
Section: Discussionmentioning
confidence: 67%